Mengapa PBL (Masih) Diperdebatkan di Fakultas Kedokteran? - Elisabeth Rukmini (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Problem-based learning (PBL) has been implemented widely in most of faculty of medicine in Indonesia. Nevertheless, PBL as a learning method is still debated. This article tried to unravel the debate of PBL implementation in medical schools, as well as recommending important notes in order to find a well-defined PBL and to improve its implementation. PBL should be acknowledged as one of the student centered learning methods. Therefore, this condition would not rule out the possibility of the empirical progress in PBL implementation in faculty of medicine in Indonesia.